2015
DOI: 10.1242/jeb.112003
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of heart rate responses to acute stressors throughout the breeding season in a colonial seabird, the king penguin

Abstract: ABSTRACT'Fight-or-flight' stress responses allow animals to cope adaptively to sudden threats by mobilizing energy resources and priming the body for action. Because such responses can be costly and redirect behavior and energy from reproduction to survival, they are likely to be shaped by specific life-history stages, depending on the available energy resources and the commitment to reproduction. Here, we consider how heart rate (HR) responses to acute stressors are affected by the advancing breeding season i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…We found that brooding king penguins initiated more agonistic interactions than incubating birds, which is consistent with previous findings (Côté, ) and with the idea that parents are willing to invest more into territorial defense with an increasing reproductive value of their chick (Côté, ; Viblanc, Dobson, et al, ; Viblanc, Gineste, et al, ; Viblanc, Smith, Gineste, Kauffmann, & Groscolas, ). Interestingly, brooding birds were also more strongly lateralized than incubating birds, which might be explained by a gradual increase in predation risk (e.g., by brown skuas) around the time of chick brooding (Descamps et al, ) (see c above).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that brooding king penguins initiated more agonistic interactions than incubating birds, which is consistent with previous findings (Côté, ) and with the idea that parents are willing to invest more into territorial defense with an increasing reproductive value of their chick (Côté, ; Viblanc, Dobson, et al, ; Viblanc, Gineste, et al, ; Viblanc, Smith, Gineste, Kauffmann, & Groscolas, ). Interestingly, brooding birds were also more strongly lateralized than incubating birds, which might be explained by a gradual increase in predation risk (e.g., by brown skuas) around the time of chick brooding (Descamps et al, ) (see c above).…”
Section: Discussionsupporting
confidence: 92%
“…Sex-dependent lateralization may then be an efficient way to confuse predators as to vigilance behavior related to visually active fields, all while being able to save energy for instance via unihemispheric sleep, a faculty known to exist only in birds and aquatic mammals (Rattenborg, Lima, & Amlaner, 1999). This is all the more relevant for breeding penguins where energy sparing of stored body reserves while fasting on-land is critical to successful breeding (Gauthier-Clerc, Maho, Gendner, Durant, & Handrich, 2001;Groscolas & Robin, 2001;Olsson, 1997 We found that brooding king penguins initiated more agonistic interactions than incubating birds, which is consistent with previous findings (Côté, 2000) and with the idea that parents are willing to invest more into territorial defense with an increasing reproductive value of their chick (Côté, 2000;Viblanc, Dobson, et al, 2016;Viblanc, Smith, Gineste, Kauffmann, & Groscolas, 2015). Interestingly, brooding birds were also more strongly lateralized than incubating birds, which might be explained by a gradual increase in predation risk (e.g., by brown skuas) around the time of chick brooding (Descamps et al, 2005) .…”
Section: Discussionsupporting
confidence: 89%
“…acute stress responses (both HPA and sympathetic) and reactivity to external threats (Viblanc et al, 2016(Viblanc et al, , 2015(Viblanc et al, , 2014a(Viblanc et al, ,b, 2012a, possibly explaining the high inter-individual variability observed in our study. CORT plays major roles in the breeding cycle of penguins.…”
Section: Hormonal and Metabolic Responses To Acute Stressmentioning
confidence: 68%
“…capture and restraint. Sympathetic heart rate responses to stress are stressor-specific in this species, and captures are known to elicit maximal adrenergic responses when compared to milder stressors such as loud sounds or distant human approaches (Viblanc et al, 2015(Viblanc et al, , 2012a. Whether HPA responses are also stressor-specific (e.g.…”
Section: Hormonal and Metabolic Responses To Acute Stressmentioning
confidence: 95%
“…Even then, the prognostic quality of 151 HR itself is tenuous in clinical medicine. In humans, a typical standard deviation of heart 152 rate can be up to 10 beats per minute, which is not itself significantly different from window into the stress state of an animal is challenging from a taxonomic, 163 environmental, circadian, and life history perspective, as they are all factors that affect 164 HR and HR-associated adaptations (Viblanc et al 2015). Therefore, a cardiac measure 165 that provides more resolution into the underlying physiology is required and may be 166 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 blood circulation and delivery of nutrients and glucose to peripheral organs.…”
mentioning
confidence: 99%